MEMBANGUN KINERJA MAHASISWA PLP MELALUI POLA LESSON STUDY - Jauhari, Agus (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2011)
The effort of learning community development among Physics student in PLP, lecture by using pattern Lesson Study. Tuition in lesson plan with cooperation pattern. Cooperation between PLPâs student attention focus in: formatting of RPP, structure, model, scenario, appliance test-drive and media, evaluation, test-drive, and observation of lesson. Frequency/communications lesson plan is measured by observation and interview to student, while broadness and deepness of discussion/communications lesson plan, is measured by observation and interview to teacher. Research indicated that make-up of cooperation between student in drawing up study plan. Discussion intensity/student communications of the PLPâs student that use Lesson Study pattern are better than the studentâs that doesnât use it.Keyword: community learning, lesson study, lesson plan